2020
DOI: 10.1590/2177-6709.25.3.031-038.oar
|View full text |Cite
|
Sign up to set email alerts
|

Shear bond strength evaluation of metallic brackets bonded to a CAD/CAM PMMA material compared to traditional prosthetic temporary materials: an in vitro study

Abstract: Introduction: Orthodontic treatment for adults is currently increasing, and therefore the need to bond brackets to restorations and temporary crowns. The use of CAD/CAM PMMA provisional restorations for orthodontic purposes have not yet been described, and there is currently insufficient information regarding the strength of bracket adhesion. Objective: This study aimed at evaluating the effects of thermocycling (TC) and surface treatment on shear bond strength (SBS) of brackets to different provisional mate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…In orthodontic practice, obtaining optimal SBS rather than the maximum possible SBS is preferable [ 32 ]. Brackets bonded to fixed prosthodontic surfaces should be compatible to resist the oral biomechanics, masticatory forces, and functional activities of the patient, but also adequate enough to facilitate debonding upon treatment completion without any deleterious effect on the bonded surface of the restoration [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…In orthodontic practice, obtaining optimal SBS rather than the maximum possible SBS is preferable [ 32 ]. Brackets bonded to fixed prosthodontic surfaces should be compatible to resist the oral biomechanics, masticatory forces, and functional activities of the patient, but also adequate enough to facilitate debonding upon treatment completion without any deleterious effect on the bonded surface of the restoration [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Poly(methyl methacrylate) (PMMA) [(C5O2H8)n] based bone cements belong to a group of synthetic nondegradable, biocompatible polymeric hard biomaterials. Acrylic bone cements have versatile applications such as: cemented hip implants [1], spinal treatments [2], custom made bone implants [3], dental applications like orthodontic brackets [4] and occlusal splints [5]. PMMA is an isotropic, elasto-visco-plastic solid and amorphous/glassy polymer material.…”
Section: Introductionmentioning
confidence: 99%
“…Nguyen et al [10] considered a cyclic fatigue crack growth as the major governing factor of the bone cement failure, considering approximately five million steps per year for one person, meaning that the joint prosthesis should endure around 10 8 cyclic motions during its lifetime. Also, in dentistry, steel brackets are in close contact with PMMA [4]. On the other hand, articulating surfaces of loose joint replacements generate wear debris during the contact.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During orthodontic treatment, brackets and other attachments are bonded on provisional restorations and forces are applied conventionally. However, several studies have revealed that PMMA achieves low bond strength with resin cement or composite, [1][2][3][4][5] indicating that attachments have a higher risk of debonding.…”
Section: Introductionmentioning
confidence: 99%